The Possibilities of Dynamic Shipment Weighing in Rail Freight Transport - Lizbetin, Jan; Vejs, Petr; Caha, Zdenek; Lizbetinova, Lenka; Michalk, Philip (Communications - Scientific letters of the University of Zilina, 2016)
This article deals with an analysis of the methods of the dynamic weighing of rail vehicles. The measurement of axle load (both static and dynamic) is one of the current standard processes within the technical specifications for interoperability (TSI).